Konstruksi Pendidikan Gender Pada Anak Dalam Keluarga Dual-Earner di Kota Makassar - Sadriani, Andi; Suhaeb, Firdaus W (Peneliti.net, 2026)
This study aims to analyze the construction of gender education for children in families with two working parents in Makassar City. The background of this study is based on the increasing participation of both parents in the workforce, which is not always followed by changes in equal parenting practices. This study focuses on the division of parenting roles, the process of socialization of gender values, and children's responses to gender education in the family. This study uses a qualitative approach with a case study type, involving 10 families with two working parents as informants who were selected purposively. Data collection techniques were carried out through in-depth interviews, observation, and documentation, which were then analyzed through the stages of reduction, presentation, and drawing conclusions. The results of the study indicate that the division of parenting roles is still dominated by mothers, while fathers tend to play a supporting role. The socialization of gender values ​​occurs implicitly through daily practices and still shows ambivalence between traditional and modern values. Meanwhile, children show an active response, not only imitating but also interpreting and questioning accepted gender values. The conclusion of this study confirms that families with two breadwinners have not yet fully created egalitarian relationships, but have the potential to become a space for the transformation of gender values. Therefore, more reflective awareness and better parenting practices are needed to promote gender equality education from an early age.